2016
DOI: 10.1161/atvbaha.115.306954
|View full text |Cite
|
Sign up to set email alerts
|

Factor XI Deficiency Protects Against Atherogenesis in Apolipoprotein E/Factor XI Double Knockout Mice

Abstract: Objective Atherosclerosis and atherothrombosis are still major causes of mortality in the Western world, even after the widespread use of cholesterol-lowering medications. Recently, an association between local thrombin generation and atherosclerotic burden has been reported. Here, we studied the role of factor XI (FXI) deficiency in the process of atherosclerosis in mice. Approach and Results Apolipoprotein E/FXI double knockout mice, created for the first time in our laboratory. There was no difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 41 publications
2
42
1
Order By: Relevance
“…The idea to search for the relationship between FXI deficiency and pneumonia came from the following observations: (i) a reduced influx of leucocytes to the site of infections and inflammation has been reported in diverse mice models involving FXI KO mice in comparison with wild‐type mice . (ii) A prominent reduction in macrophage infiltration has been found in the atherosclerotic lesions in apo E/FXI KO mice in comparison with apoE KO mice . (iii) Human neutrophils have a reduced capacity to phagocytose bacteria when the activation of FXI is inhibited .…”
Section: Discussionmentioning
confidence: 99%
“…The idea to search for the relationship between FXI deficiency and pneumonia came from the following observations: (i) a reduced influx of leucocytes to the site of infections and inflammation has been reported in diverse mice models involving FXI KO mice in comparison with wild‐type mice . (ii) A prominent reduction in macrophage infiltration has been found in the atherosclerotic lesions in apo E/FXI KO mice in comparison with apoE KO mice . (iii) Human neutrophils have a reduced capacity to phagocytose bacteria when the activation of FXI is inhibited .…”
Section: Discussionmentioning
confidence: 99%
“…Mice with deficiency in apolipoprotein E ( Apoe −/− ) spontaneously develop atherosclerotic lesions, but Apoe −/− mice with genetic FXI deficiency show reduced atherosclerosis progression. 56 Moreover, anti-FXI ASO treatment reduces thrombus formation and fibrin deposition in a model of plaque rupture in Apoe −/− mice. 57 Thus, FXI inhibition may also be effective for reducing arterial thrombosis in humans.…”
Section: Effects Of Antithrombotic and Hemostatic Agents On Fibrinmentioning
confidence: 99%
“…While reduced fibrin deposition may have a role in the tissue sparing effect, alteration of the inflammatory response could be involved. Shnerb-Ganor et al reported that fXI deficiency reduces atherosclerotic plaque growth and plaque infiltration by macrophages in ApoE deficient mice [35]. van Montfoort et al also noted reduced macrophage infiltration and an absence of neutrophils in arteries in ApoE-null mice after knockdown of fXI expression [36].…”
Section: Factor XI and Inflammation – Animal Modelsmentioning
confidence: 99%